A finite element analysis study based on valgus impacted femoral neck fracture under diverse stances. Issue 5 (4th April 2022) - Zhang, Haowei; Xu, Xinsheng; Wu, Shenghui; Liu, Ying; Mei, Jiong
Abstract: The aim of the study was to determine the biomechanical environment of patients who suffer from valgus impacted femoral neck fracture. With the help of computational modeling, both of finite element hip fracture and normal three-dimensional model were reconstructed from a patient with hip fracture. The predicted stress distribution was compared between before and after fracture. After the fracture, during standing and the gait, the fracture site has a greater change in stress distribution due to the shortening of the femoral neck. The largest stress occurs at the middle and lower end of the femoral shaft, which occurs from toe off to deceleration during the whole gait. After the fracture, greater stress on the femoral head will result in a worse mechanical environment for the femur. The stress peak value of the femoral shaft is larger than the unfractured side and the stress distribution is uneven. From the results of gait analysis, it is concluded that the increase of concentrated stress and the change of stress distribution will cause the possibility of secondary fractures at the middle and lower ends of the femoral shaft when there is an accident in the case of existing fracture.